Implementation of tools for designing and generating of programs on the basis of algebra of algorithms with data - Akulovskiy, V.G.; Doroshenko, А.Yu.; Yatsenko, O.A. (Інститут програмних систем НАН України, 2017)
The development of the algebra-algorithmic toolkit for designing and synthesis of programs for constructing of specifications of algorithms, which combine common definition of data and execution processes in algebra of algorithms with data, is proposed. The application of the proposed algebraic approach and the toolkit is illustrated on the example of the development of sorting programs.